Effects of high electric fields on microorganisms: II. Mechanism of action of the lethal effect - Hamilton, W.A.; Sale, A.J.H. (Biochimica et biophysica acta. General subjects, 1967)
1. 1. The mechanism by which high electric field strengths, delivered as a series of pulses of direct current, kill vegetative bacterial cells in suspension has been studied. Membrane damage was demonstrated by the lysis of erythrocytes and protoplasts, the leakage of intracellular contents, the loss of the ability of Escherichia coli to plasmolyze in a hypertonic medium and the release of β-galactosidase activity in a permease-negative mutant of E. coli. In a suspension of Staphylococcus aureus the number of cells killed by an electric field correlated with the number that could not be converted to spheroplasts. 2. 2. Spores of Bacillus cereus and Bacillus polymyxa were resistant to electric field strengths up to 30 kV cm. The development of sensitivity during germination and outgrowth was due to the emergence of the vegetative cell from the protection afforded by the spore coat and cortex layers. 3. 3. The d.c.-pulse treatment caused loss of motility and synthesis of the induced enzyme β-galactosidase in vegetative bacteria, but no inhibitions were demonstrated with a number of isolated enzyme activities. 4. 4. It is proposed that the electric field causes an irreversible loss of the membrane's function as the semipermeable barrier between the bacterial cell and its environment, and that this is the cause of cell death.